Delayed Yet Successful Mechanical Thrombectomy for Phlegmasia Cerulea Dolens in a Limb with Severe Arterial Disease and May-Thurner Syndrome. (2nd November 2020) - Said, Ahmad; Kraft, Phillip; Sayed, Luay
Abstract : Phlegmasia cerulea dolens (PCD) is a rare but life-threatening complication of acute deep venous thrombosis that lacks consensus regarding the approach to management. We present a case of PCD developing shortly after a spinal surgery and manifesting as acute swelling and discoloration in a leg with existing severe atherosclerotic arterial disease. The patient's critical limb ischemia was completely and rapidly reversed by percutaneous mechanical thrombectomy using the ClotTriever device despite a delay in treatment. An underlying iliac vein compression "May-Thurner" syndrome was discovered using intravascular ultrasound and treated with angioplasty. This case identifies mechanical thrombectomy using the ClotTriever system as a possible effective and safe treatment for PCD.